Clinical Application of Vimana Sthana of Charaka Samhita in the Present Era (AYUSHDHARA, 2023)
From last few decades in health sector of India, role of traditional medicine enhanced whether it is Ayurveda, Siddha, Unani or Yoga. Ayurveda main aim is to maintain the health of the healthy individual and treatment of the ailments. This treatment related concept with their fundamentals were written in stepwise manner and classified in various Sthana. This article highlights the ancient view of Charaka and clinical applications of the concepts embedded in the Vimana Sthana of Charaka Samhita. Aims and Objectives: To explore the concepts clinical application of Vimana Sthana of Charaka Samhita in the present era. Material and Methods: The available Samhita mainly Charaka Samhita, with Sanskrit and Hindi commentaries on Vimana Sthana along with the available commentaries. Discussion: According to Acharya Charaka, Vimana Sthana is explained after Nidana Sthana where all the etiological factors are explained properly but still if a physician does not know the measurement and special features of Doshas he will not be able to treat the patient properly. There is total eight chapters in this Sthana having wide variety of topics that a clinician should know before entering into practice. Chapter wise clinical applicability are discussed. Conclusion: Approach to diseases concept by Acharya Charaka in Vimana Sthana is progressive, scientific and applied in clinical application of today’s era also.